Mud volcanoes and gas vents in the Okhotsk Sea area - Shakirov, R. B.; Obzhirov, A.; Suess, Erwin (Geo-Marine Letters, 2004)
Gas emissions from mud volcanoes on Sakhalin Island and water-column gas flares arising from cold seeps in the Okhotsk Sea appear to be related. They are likely activated by tectonic movements along the transform plate boundary separating the Okhotsk Sea Plate from the Eurasian and Amur plates. Gas vents (flares) and methane anomalies occur in the waters offshore Sakhalin Island, along with NE-SW-trending mounds and fluid escape structures on the seafloor. The intersection of the NE-striking transverse faults on land with the Central Sakhalin and Hokkaido-Sakhalin shear zones apparently determines the sites of mud volcanoes, a pattern that continues offshore where the intersection with the East Sakhalin and West Derugin shear zones determines the sites of the submarine gas vents.